Free-spirit shawls : 20 eclectic knits for every day - Shroyer, Lisa (Interweave Press, 2012)
"Free-Spirit Shawls features 20 shawl projects-including top-down triangle, crescent, and semi-circular. While some projects feature the stockinet-plus-lace designs driving the current shawl and shawlette craze, others explore textured stitches, simple color work and stripes, and unusual stitch patterns. Technique features forcus on special skills such as Shetland construction. Lisa also takes care to push designers beyond the current trends, making this book relevant for some years to come. Technical essays on top-down, bottom-up, side to side, crescent, and circular constructions will mix with tutorials on knitting attached edgings, finishing, blocking, and how to best use hand-painted yarns. The style of the book closely aligns with the Knitscene aesthetic, a style that draws largely from indie trends in both fashion and the online knitting community. Yarn choices, colors, and presentation fit seamlessly with what these shawl knitters see on their favorite knitting blogs, on Ravelry, and in the independently-published booklets they purchase. "--